Poverty and Agriculture in the Philippines: Trends in Income Poverty and Distribution - Aubrey D. Tabuga; Celia M. Reyes; Ronina D. Asis; Maria Blesila G. Datu (Philippine Institute for Development Studies (PIDS), 2012)
Poverty incidence in the Philippines is rising based on the national official data released by the National Statistical Coordination Board. Poverty incidence among population rose from 24.9 percent in 2003 to 26.4 percent in 2006 and then inched up further to 26.5 percent in 2009. This is in reverse of the downward trend and is a major deviation from the path toward achieving the Millennium Development Goals. The disparities across the regions remain wide both in terms of poverty and inequality measures. In this paper, we show the salient features of the country's poverty situation in a hope to contribute to the existing knowledge about the poverty condition and to the formulation of better strategies for reducing poverty. It focuses on agriculture because it plays a central role in the poverty condition that continues to persist despite recent episodes of high economic progress the country has achieved.
Keywords: 330; inequality; Philippines; Philippine poverty profile; agricultural poverty; multidimensional poverty